After the fall: Regulatory focus, trust and negotiators' responses to a crisis. Issue 1 (2nd January 2017) - Caspi, Plia Vaisman; Olekalns, Mara; Druckman, Daniel
ABSTRACT: In two experiments, we evaluated how negotiators' intra- and interpersonal risk preferences influenced their actions following a crisis during their negotiation. To establish differences in risk preferences, we manipulated negotiators' regulatory focus (intrapersonal risk) and trust in their opponent (interpersonal risk). In Experiments 1 and 2, we showed that negotiators who were in fit (promotion focus, affect-based trust; prevention focus, cognition-based trust) were more likely to favor the more risky option of continuing to negotiate with a new strategy than negotiators who were not in fit (promotion focus, cognition-based trust; prevention focus, affect-based trust). In E2, we also compared benign and adversarial environments by manipulating trust level (low vs high). Trust level, rather than influencing strategy following a crisis, influenced negotiators' willingness to take risks to reach agreement: Distance from agreement did not influence negotiators' willingness to take risks when trust was low but, when trust was high, willingness to take risks increased as distance from agreement increased. Finally, we showed that the importance of reaching a favorable agreement was influenced by both trust level and distance from agreement when negotiators had a promotion focus but not when they had a prevention focus. Implications for theory and practice are discussed.